Keperluan Personal Dan Profesional Guru Matapelajaran Kemahiran Hidup - Ismail, Othman (2002)

(untitled)
The objective of the study is to identify the level of personal and professional needs and also to determine its relationship with job dimension, job environment, students and professionalism dimension. The job dimension being studied were salary, coworkers, current job, promotion, supervision, while dimension of students covering student's academic and discipline, and for the professionalism dimension related to professional image and development. Differences of level of needs according to gender, ages and salary were also studied. Sample of survey consisted of Kemahiran Hidup teachers from twelve selected secondary schools located in Sungai Petani, Kedah Darul Aman. They needed to gve responses on 45 items in the questionnaire. Statistic explanation in the form of percentage (%) and inferential statistic whch are 2 ways t-test, one-way ANOVA (F-test) and Pearson Correlation (r) used to analyze the data using the Statistical Packages for the Social Sciences 10.0 (SPSS) program. Result of this study showed strong and significant positive relationship exists between level of needs with salary, current job, promotion, supervision, job environment, students dimension, professional image and development. Relationship between level of needs with co-workers, students' academic and discipline is significantly moderate relationship. The result of t-test showed there is no significant difference between level of needs with male and female teachers. The result from one-way ANOVA showed that there exist significant differences between levels of needs with level of salary but otherwise with the level of ages. 80.2% of respondents gave responses at highest order of the personal needs on aspect that current job as teacher is secured. 51.O% respondents gave statement that the lowest order of personal needs is chances for promotion. From the point of professional needs, 77.1% respondents have achieved highest order in the professional image that is in the way of feeling proud towards professional. 32.3 % respondents cited that professional needs at the lowest level in professional development is the funding to improve professionalism.